IGBO NEGATIVE MORPHEME VARIATION: A STUDY OF OPI NSUKKA DIALECT - Eze, Cyprian Chidozie (EBSU Journal of Social Sciences and Humanities, 2023)
Dialects can be described as the different varieties of a particular language. Opi dialect is a subdivision of the Igbo standard form. Now, many find it difficult to understand the dialect because some variations. For this some question their being Igbo. The Opi dialect speakers communicate Igbo speakers using the standard form of the language. This study is the researcher’s contribution to preserve the dialect as well as to give insight to Opi dialect researchers for further investigations. The aim of this study is to compare negative morphemes in opi dialect and that of the Standard Igbo in order to ascertain the areas of differences and similarities between the two. The researcher focused on the negation because of the sharp difference between that of the Opi dialect and the standard Igbo. The researcher is a native speaker of Opi dialect thus an intuitive knowledge of the dialect by the researcher is used to collect data and validated by other native speakers of the same dialect. the theoretical basis in which this study is based on is the Wave and the Accommodation Theories. The findings are: The negative morphemes in Opi dialect differ drastically from that of the standard Igbo form. Some negative morphemes in Opi dialect do not have any vowel attached to it. For example: ‘g’, and ‘dg’ replace ‘ghi/ghị in standard Igbo. Also ‘le’and ‘lε’ replaces ‘la’ in standard Igbo. Both dialects have slight differences in their negative morphemes and are the same language.